Mathematics Anxiety and Self-efficacy among Secondary School Students - Risma Nurul Auliya (Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai-Nilai Islami), 2017)
The aims of this research are intended to examine the effect of mathematics anxiety towards mathematics self-efficacy among secondary school students. The research utilized a survey method with quantitative approach. The population in this research are all of students from one of junior high school in Depok. As concern, the sample are grade eight students., who selected by using purposive sampling technique. The quantitative analysis is used linear regression analysis. The result shows the negative effect of mathematics anxiety towards mathematics self-efficacy.